SAT0152 EFFICACY OF BARICITINIB IN PATIENTS WITH MODERATE-TO-SEVERE RHEUMATOID ARTHRITIS WITH 3 YEARS OF TREATMENT: RESULTS FROM A LONG-TERM STUDY. (2nd June 2020) - Smolen, J. S.; Xie, L.; Jia, B.; Taylor, P. C.; Burmester, G. R.; Tanaka, Y.; Elias, A.; Cardoso, A.; Ortmann, R.; Walls, C.; Dougados, M.
Abstract : Background: Baricitinib (Bari) is an oral, selective and reversible Janus kinase 1 and 2 inhibitor approved for the treatment of adults with active RA. In addition to long-term safety which has been disclosed previously with data up to 7 years [1], an important clinical consideration is whether treatment efficacy can be maintained over the long term. Objectives: To evaluate the long-term efficacy of once-daily Bari 4 mg in patients with active rheumatoid arthritis (RA) who were either naïve to or who had inadequate response (IR) to methotrexate (MTX) Methods: Post hoc analyses of data from two phase 3 studies, RA-BEGIN (MTX-naïve) and RA-BEAM (MTX-IR) for 52 weeks, and one long-term extension (LTE) study (RA-BEYOND) for an additional 96 weeks were conducted (148 weeks in total). At week 52, MTX-naïve patients initially treated with MTX monotherapy, Bari 4 mg monotherapy, or Bari 4 mg +MTX in RA-BEGIN were switched to open-label Bari 4 mg monotherapy for treatment in the LTE. Similarly, at week 52, MTX-IR patients initially treated with Bari 4 mg [+ background MTX noted as (+MTX) for RA-BEAM] or adalimumab (ADA) (+MTX) in RA-BEAM were switched to open-label Bari 4 mg (+MTX) for treatment in the LTE. Patients who received placebo (+MTX) were switched to open-label Bari 4 mg (+MTX) at week 24. The analyses of efficacy (SDAI) and physical function (HAQ-DI) were conducted on all patients who were randomized into the RA-BEGIN and RA-BEAM studies and had received ≥1 dose of study drug after randomization (mITT population). The proportion of patients who reached low disease activity (LDA), as measured by SDAI ≤11, was evaluated along with change from baseline in HAQ-DI. The non-responder imputation (NRI) method was used for the categorical analysis. Results: By week 24 in RA-BEGIN (N=584), 62% of patients treated with Bari 4 mg monotherapy or Bari 4 mg +MTX achieved SDAI LDA in comparison to 40% of pts in the MTX monotherapy group; response rates seen at week 24 in the Bari treatment groups were maintained through week 148 (Fig 1A ). Similarly, by week 24 in RA-BEAM (N=1, 305), 52% of patients treated with Bari 4 mg (+MTX) and 50% of patients treated with ADA (+MTX) achieved a SDAI LDA in comparison to 26% of patients from the PBO (+MTX) group. The response rate seen at week 24 with Bari 4 mg and ADA were maintained through week 148, even after patients switched from ADA to Bari 4 mg at week 52 (Fig 1B ). Similar improvement and maintenance patterns in physical function measured by HAQ-DI were demonstrated. The overall discontinuation rate across treatment groups from RA-BEGIN (19.5%) and RA-BEAM (14.2%) have been published. In the LTE, the discontinuation rate from Bari treatment was 13.7% for patients originating from RA-BEGIN (1.1% due to lack of efficacy, 6.4% due to safety) and 12.6% for patients originating from RA-BEAM (1.8% due to lack of efficacy, 5.9% due to safety). Conclusion: Long-term treatment with Bari 4 mg demonstrated the maintenance of clinically-relevant outcomes for up to 3 years. Low discontinuation rates during the LTE indicated that Bari 4 mg treatment was well-tolerated. References: [1]Genovese et al. Annals of the Rheumatic Diseases . 2019;78:308-309. Disclosure of Interests: Josef S. Smolen Grant/research support from: AbbVie, AstraZeneca, Celgene, Celltrion, Chugai, Eli Lilly, Gilead, ILTOO, Janssen, Novartis-Sandoz, Pfizer Inc, Samsung, Sanofi, Consultant of: AbbVie, AstraZeneca, Celgene, Celltrion, Chugai, Eli Lilly, Gilead, ILTOO, Janssen, Novartis-Sandoz, Pfizer Inc, Samsung, Sanofi, Li Xie Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, Bochao Jia Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, Peter C. Taylor Grant/research support from: Celgene, Eli Lilly and Company, Galapagos, and Gilead, Consultant of: AbbVie, Biogen, Eli Lilly and Company, Fresenius, Galapagos, Gilead, GlaxoSmithKline, Janssen, Nordic Pharma, Pfizer Roche, and UCB, Gerd Rüdiger Burmester Consultant of: AbbVie Inc, Eli Lilly, Gilead, Janssen, Merck, Roche, Pfizer, and UCB Pharma, Speakers bureau: AbbVie Inc, Eli Lilly, Gilead, Janssen, Merck, Roche, Pfizer, and UCB Pharma, Yoshiya Tanaka Grant/research support from: Asahi-kasei, Astellas, Mitsubishi-Tanabe, Chugai, Takeda, Sanofi, Bristol-Myers, UCB, Daiichi-Sankyo, Eisai, Pfizer, and Ono, Consultant of: Abbvie, Astellas, Bristol-Myers Squibb, Eli Lilly, Pfizer, Speakers bureau: Daiichi-Sankyo, Astellas, Chugai, Eli Lilly, Pfizer, AbbVie, YL Biologics, Bristol-Myers, Takeda, Mitsubishi-Tanabe, Novartis, Eisai, Janssen, Sanofi, UCB, and Teijin, Ayesha Elias Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, Anabela Cardoso Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, Robert Ortmann Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, Chad Walls Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, Maxime Dougados Grant/research support from: AbbVie, Eli Lilly, Merck, Novartis, Pfizer and UCB Pharma, Consultant of: AbbVie, Eli Lilly, Merck, Novartis, Pfizer and UCB Pharma, Speakers bureau: AbbVie, Eli Lilly, Merck, Novartis, Pfizer and UCB Pharma